Effects of epigallocatechin-3-gallate (EGCG) on the developmental competence of parthenogenetic embryos in pig - Zhao Namula; Vien Luu Viet; Takeshige Otoi; Yukine Kaedei; Fuminori Tanihara; Hideaki Naoi; Morteza Yavari (Italian Journal of Animal Science, 2010)
This study was conducted to examine the effects of (-)-epigallocatechin gallate (EGCG) supplementation on the developmental competence and quality of parthenogenetic porcine embryos during culture. Parthenogenetic embryos derived from in vitro matured oocytes were cultured for 8 days in a modified North Carolina State University (NCSU)-37 solution supplemented with EGCG at different concentrations (0, 1, 5, 10, and 50 µM). Supplementation of 1 and 5 µM EGCG during in-vitro culture of embryos showed no significant influence on the rate of cleavage or that of blastocyst formation, or on the total cell number and DNA fragmentation indices of blastocysts when compared to those of a control group. However, when 10 and 50 µM EGCG were supplemented into the culture medium, the cleavage rates were significantly lower than those of the other groups. No embryo developed to the blastocyst stage. Results show that treatment with low EGCG during in vitro culture has no influence on the developmental competence of porcine embryos, but the presence of high concentrations of EGCG is apparently harmful for in vitro development of porcine parthenotes.